2011
DOI: 10.1007/s00253-011-3398-9
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamic study of an internal airlift reactor for microalgae culture

Abstract: Internal airlift reactors are closed systems considered today for microalgae cultivation. Several works have studied their hydrodynamics but based on important solid concentrations, not with biomass concentrations usually found in microalgae cultures. In this study, an internal airlift reactor has been built and tested in order to clarify the hydrodynamics of this system, based on microalgae typical concentrations. A model is proposed taking into account the variation of air bubble velocity according to volume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 29 publications
0
10
0
1
Order By: Relevance
“…This velocity can be considered as the transition from regimes I to regime II as the gas holdup in the downcomer was very low (∼1 %). In previous studies, the no‐bubble phase or very low gas holdup in the downcomer were found for V g well below 0.01 m/s . Similarly, for the same experimental setup, Klein et al observed the onset of bubble dispersion in the downcomer for 0.008 < V g < 0.02 m/s.…”
Section: Resultsmentioning
confidence: 59%
See 1 more Smart Citation
“…This velocity can be considered as the transition from regimes I to regime II as the gas holdup in the downcomer was very low (∼1 %). In previous studies, the no‐bubble phase or very low gas holdup in the downcomer were found for V g well below 0.01 m/s . Similarly, for the same experimental setup, Klein et al observed the onset of bubble dispersion in the downcomer for 0.008 < V g < 0.02 m/s.…”
Section: Resultsmentioning
confidence: 59%
“…In previous studies, the no-bubble phase or very low gas holdup in the downcomer were found for V g well below 0.01 m/s. [26,30] Similarly, for the same experimental setup, Klein et al [21] observed the onset of bubble dispersion in the downcomer for 0.008 < V g < 0.02 m/s. This means the onset of regime II can be found around this superficial gas velocity range.…”
Section: Effect Of Gas Flow Rate On Flow Regimesmentioning
confidence: 76%
“…For example, for a bubble diameter of 50 mm, the volume gas fraction of 0.075 is extremely high compared to other experimental work in similar airlift reactors using larger bubble sizes such as results reported by Rengel et al (2012). These authors give a maximum downcomer volume fraction of around 0.045 but to achieve this they require a superficial gas velocity of 0.047 m/s which is two orders of magnitude greater than that used in this work (0.00044 m/s).…”
Section: Results and Discussion Of Simulation Studymentioning
confidence: 64%
“…Our work uses a size‐adjustable riser and streamlined trumpet‐shaped hood in contrast to the three size‐fixed funnel internals . This streamlined hood changes the flow direction of the gas–fluid mixture gently before it enters the top half of the reactor, which causes most of the gas–liquid mixture to be circulated in the bottom half of the reactor . Meanwhile, the arch‐shaped holes in the bottom side of riser also create favourable hydraulic conditions for complete circulation of the gas–fluid mixture.…”
Section: Resultsmentioning
confidence: 99%